On the identification of the effect of education on health: A comment on Fonseca et al. (2020) - Pedro Albarran; Marisa Hidalgo-Hidalgo; I\~nigo Iturbe-Ormaetxe (SERIEs - Journal of the Spanish Economic Association, 2022)
In this note we revisit the paper by Fonseca et al. (Series 11: 83-103, 2020) who find that education has a positive effect on health. They use several compulsory schooling reforms as instruments for education. Our objective is to replicate this causal finding, so we start by thoroughly discussing their identification strategy. In particular, we emphasize the importance of carefully defining birth cohort groups and using country-specific time trends. Once we take these issues into account, we show that the instrument they use is too weak.
Keywords: I1; I2; 330; Compulsory schooling laws; Education; Health; Instrumental variables